Pengaruh Unsur-Unsur Struktur Pengendalian Intern pada Non Performing Loan di Lembaga Perkreditan Desa Kota Denpasar - Listika Dewi, I Gusti Agung; Widhiyani, Ni Luh Sari (E-Jurnal Akuntansi; Vol 25 No 1 (2018), 2018)
This study aims to empirically prove the effect of internal control elements on non performing loans in LPD Denpasar City. The data used in this study are primary data in the form of answers to questionnaires and secondary data in the form of LPD non-performing loans. The sample used was 35 LPDs in Denpasar City. Sampling using nonprobability sampling method with saturated sample technique. The analysis technique used in this study is multiple linear regression. The analysis results can be understood that the control environment and risk assessment have a negative effect on non-performing loans. This shows that the better the risk control and assessment environment is applied, the lower the level of non-performing loans. Control and monitoring activities have a negative effect on non-performing loans. This shows that controlling and monitoring activities carried out optimally will reduce the occurrence of non-performing loans. Keywords: non performing loan, elements of internal control structure